Public health safety literacy and its influencing factors among residents in four provinces of China - Yan NING; Xiao-hui HOU; Xiao-yan WANG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo explore the status and influencing factors of public health safety literacy (PHSL) among residents in four provinces of China for providing references to the development of appropriate intervention strategies. MethodsWe recruited 2 809 urban and rural residents aged 15 - 69 years in three provinces (Hubei, Guangdong and Sichuan) and Beijing municipality using stratified multistage cluster sampling and conducted an on-site self-administered electronic questionnaire survey among the residents during April - June, 2021. A scale with three domains (each with a maximum score of 40) was designed to assess the PHSL of the residents. T-test, one-way analysis of variance (ANOVA), and χ2 test were adopted in univariate analysis and logistic regression in multivariate analysis. Results For all the participants, the mean overall PHSL score was 81.61 ± 13.71 and the mean domain scores were 29.21 ± 5.89 for PHS perception, 25.10 ± 5.10 for PHS knowledge, and 27.30 ± 4.87 for PHS skills. There were 80.85% of the participants being assessed with basic PHSL (with the overall scale score of ≥ 72) and there were 86.69%, 61.05%, and 78.96% of the participants being assessed with basic PHS perception, knowledge, and skills (with the domain scores of ≥ 24); also based on the scale of overall score of ≥ 96 and domain scores of ≥ 32, the proportion of the participants with good PHSL was 15.70% and the proportions of participants with good PHS perception, knowledge and skills were 35.32%, 14.03% and 20.15%, respectively. Multivariate logistic regression analysis showed that PHSL was associated with residential region, sex, education and household income. The participants residing in Hubei, Sichuan, and Guangdong province were less likely to have basic/good PHSL, with the odds ratios (OR) of 0.485/0.422, 0.488/0.699, and 0.389/0.566 in contrast to those residing in Beijing municipality. The participants being female (versus male: OR = 1.336/1.283), with the education of higher than primary school education or below (junior high school: OR = 1.786/1.205; senior high or vocational or technical secondary school: OR = 2.204/2.013; college and above: OR = 2.932/3.710), with the annual household income of more than 30 000 RMB yuan (30 000 - 60 000: OR = 1.660/1.648; ≥ 120 000: OR = 1.865/2.145) were more likely to have basic/good PHSL. ConclusionFor 15 - 69 years old residents in four provincial administrative regions of China, the PHSL still needs to be improved and the residents' PHSL is influenced mainly by gender, education, annual household income and residential region.